Gas sensing properties based on a doped conducting polymer/inorganic semiconductor - Campos, M.; IEEE (Ieee, 2003)
For medical diagnostic applications, there is currently a strong need for systems that comprises simple detectors. In this paper, we report the fabrication of heterojunction between p-doped polypyrrole and n-doped silicon and its possible use in the detecting of acetone. In the forward bias voltage region, the heterojunction diode exhibit a significant, fast and reversible response to acetone. The characteristics of the diodes were measured as a function of acetone vapor, temperature, polypyrrole film thickness and frequency, using current density-voltage and capacitance-voltage measurements..
Keywords: heterojunction; conducting polymer; Schottky diode; sensor; acetone